The Effects of Principal’s Leadership and Infrastructure on Teacher’s Performance - Maryodona, Maryodona; Triwidayatsih, Triwidayatsih; Eddy, Syaiful (Journal of Social Work and Science Education, 2022)
The purpose of this research is to evaluate and assess the impact of the principal's leadership and infrastructure on teacher’s performance in the SD Muara Jaya District. The regression approach was used in this study. The factors investigated in this study were principal’s leadership (X1), infrastructure (X2), and teacher’s performance. The study was then conducted in SD Negeri Muara Jaya District, OKU Regency, with 66 teachers as sample. The findings of this study reveal that leadership and school infrastructure have an impact on teacher’s performance at SD Negeri in Muara Jaya OKU, both partially and concurrently. The research concludes that the principal must focus on his leadership and infrastructure in order to improve teacher’s effectiveness at SD Negeri Muara Jaya OKU District. This study encourages school administrators and teachers to focus on their leadership and school infrastructure so that schools can shine even brighter.